Identifikasi dan persepsi penggunaan jenis elemen taman pada natah di desa adat Sangeh, Kecamatan Abiansemal, Kabupaten Badung, Provinsi Bali - Dewi, I Gusti Ayu Purnama; Sarwadana, Sang Made; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018DO - 10.24843/JAL.2018.v04.i01.p03, 2018)
Identification and perception use of types elements on yard of Sangeh traditional village, Abiansemal Sub-district, Badung Regency, Bali Province. Bali's traditional garden is one of the uniqueness in Bali. One example of a garden that is closest to its users is yard. Yard is an empty space that is open and has many functions in the life of Balinese people. Currently the arrangement and selection of elements in the ration is very important to note that the activities carried out on yard can still take place. The purpose of this research is to identify the hard elements and soft elements used in Sangeh traditional village, to identify the way people choose the elements used and to provide information about the elements used in the yard area. The results of this study indicate the type of hard elements and soft elements used in the yard. The functions and benefits of the elements used and the recommendation of the application of the elements used are based on data from interviews, questionnaires and various literature studies. The use of elements in the nat should pay attention to the function of the elements used. The use of soft lemen corresponds to the function of landscape, and spiritual function. The use of hard elements is applied wisely so that the ecological function of the yard is maintained.